2016
DOI: 10.1148/radiol.2015151484
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Imaging Biomarkers of Gas Trapping and Emphysema in COPD:3He MR Imaging and CT Parametric Response Maps

Abstract: In all ex-smokers, ADC values were significantly elevated in regions of PRM gas trapping, and VDP was quantitatively and spatially related to both PRM gas trapping and PRM emphysema. In patients with mild to moderate COPD, VDP was related to PRM gas trapping, whereas in patients with severe COPD, VDP correlated with both PRM gas trapping and PRM emphysema.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
52
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 45 publications
9
52
0
Order By: Relevance
“…16 Recently, 19 F-MRI has been shown to correlate with pulmonary function testing in COPD patients. 10,20,27 In the present study we also showed significant correlations of FD-FV with clinical lung function test parameters such as FEV1. Accordingly, FD-FV values decreased with increasing GOLD stage.…”
Section: Discussionsupporting
confidence: 79%
“…16 Recently, 19 F-MRI has been shown to correlate with pulmonary function testing in COPD patients. 10,20,27 In the present study we also showed significant correlations of FD-FV with clinical lung function test parameters such as FEV1. Accordingly, FD-FV values decreased with increasing GOLD stage.…”
Section: Discussionsupporting
confidence: 79%
“…Another study compared ventilation and perfusion defects measured on MRI with PRM measurements of emphysema and small airways disease on CT. Ventilation defects were associated with emphysema and small airways disease and diffusion measurements were significantly raised in areas of gas trapping [127]. MR technology is still in early development but does provide an advantage over CT by allowing functional imaging and importantly being radiation free.…”
Section: Other Imaging Modalitiesmentioning
confidence: 99%
“…By registering CT images acquired at full inspiration to images acquired at full expiration and applying established Hounsfield unit (HU) thresholds, regions of the lung that trap gas that are not related to emphysema, and hence may be attributed to small airway disease, can be quantified. Although measurements of gas trapping related to "functional" small airway disease generated using this technique have been shown to be reproducible over short periods of time [9] , to be correlated with pulmonary function [8] , to show spatial agreement with other imaging modalities [10] , and to be associated with longitudinal changes in forced expiratory volume in 1 s (FEV 1 ) [11] , these measurements have yet to be pathologically validated. Furthermore, measurements generated using a single HU threshold have obvious limitations, and therefore there is motivation to investigate other CT inspiratory-to-expiratory classification approaches.…”
Section: Introductionmentioning
confidence: 99%